Proposed Online Marketing Strategy for Candy Bar Chocolate and Candy Shop - Fitrina, Benty; Hariandja, Evo S. Hariandja (The Indonesian Journal of Business Administration, 2014)
Abstract – The research was conducted to form strategy in order to help Candy Bar to overcome the problems in its first year of existence. To survive in the upcoming days, the strategy for Candy Bar generated through analysis of existing 7P and company’s 5C’s situational condition. TOWS Analysis and strategy was conducted after analyzing these two components. Root problem of Candy Bar is found, many weaknesses leaked, start from weak STP and poor marketing strategy, especially promotional. Therefore, the proposed marketing strategies of Candy Bar are re-formed STP and proposed new marketing mix 7P, completed with implementation Plan which will give a clearer guidance on Candy Bar’s promotional program.   Keyword: Candy shop, Chocolate, Online, Marketing strategy, Promotion